2017
DOI: 10.2147/rru.s124200
|View full text |Cite
|
Sign up to set email alerts
|

Upward migration of ureteric stone in a military trainer: a case report

Abstract: Retrograde ureteric stone migration is an extremely rare phenomenon with only one previously reported case in the literature. We report on a case of upward spontaneous migration of a ureteric stone in a 39-year-old male military trainer in Saudi Arabia who was diagnosed with upper left ureteric stone based on non-contrast spiral computerized tomography kidney ureter bladder (CT-KUB) scan. The plan was to treat the patient conservatively with alpha blockers and oral hydration. Two weeks after treatment started,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…To our surprise the next day it migrated spontaneously upward to the renal calyx. A similar phenomenon has been observed in the first ever report of one such case by Khan Z et al and also in the canines as reported in the veterinary literature [5,10] Various other possible mechanisms for such occurance as described by Fallatah et al, include excessive exercises causing ureteric dilation proximal to the calculus or due to the kidney's response to obstruction by reducing glomerular filtration rate in the renal pelvis and upward stone migration [6] . Also, the use of nonsteroidal antiinflammatory drugs for relieving renal colic reduces the glomerular filtration rate by interrupting the renal pelvis pacemaker cells, which might reduce the ureteric peristalsis aiding the upward migration of calculi through the dilated low pressure system [11] .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To our surprise the next day it migrated spontaneously upward to the renal calyx. A similar phenomenon has been observed in the first ever report of one such case by Khan Z et al and also in the canines as reported in the veterinary literature [5,10] Various other possible mechanisms for such occurance as described by Fallatah et al, include excessive exercises causing ureteric dilation proximal to the calculus or due to the kidney's response to obstruction by reducing glomerular filtration rate in the renal pelvis and upward stone migration [6] . Also, the use of nonsteroidal antiinflammatory drugs for relieving renal colic reduces the glomerular filtration rate by interrupting the renal pelvis pacemaker cells, which might reduce the ureteric peristalsis aiding the upward migration of calculi through the dilated low pressure system [11] .…”
Section: Discussionsupporting
confidence: 71%
“…A considerable number of patients with small calculus usually experience a spontaneous expulsion. On the other hand, the upward urinary tract calculus migration has been reported only twice in the literature [5,6] To the best of our knowledge, we report the third case of retrograde migration of the urinary tract calculus and the first to be from India.…”
Section: Introductionmentioning
confidence: 75%
“…Although urolithiasis is a relatively common occurrence, fewer than 10 cases of retrograde urolithiasis migration have been documented once it has entered the ureter. The first documented case in English literature dates from 2015 in Bahrain, with a few cases in the Middle East and India documented afterwards [4][5][6][7]. Of the previously reported cases, only Fatallah et al reported relatively little distal migration of the urolithiasis before it was subsequently found to have migrated back into the calyx, whereas the other reports detail the calculus having migrated to the vesicoureteral junction before beginning its retrograde migration [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…The first documented case in English literature dates from 2015 in Bahrain, with a few cases in the Middle East and India documented afterwards [4][5][6][7]. Of the previously reported cases, only Fatallah et al reported relatively little distal migration of the urolithiasis before it was subsequently found to have migrated back into the calyx, whereas the other reports detail the calculus having migrated to the vesicoureteral junction before beginning its retrograde migration [4][5][6][7]. The previous papers report intervals of 3 days to around 2 weeks between the onset of pain and its subsequent resolution, at which point it was assumed that the calculus had been spontaneously passed, as was the case in our patient, before it was discovered to have migrated to kidney [4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%